Pharmacist’s interventions in the management of patients with chronic kidney disease (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
AimChronic kidney disease (CKD) is a complex debilitating condition affecting more than 70 million people worldwide. With the increased prevalence in risk factors such as diabetes, hypertension, and cardiovascular disease in an aging population, CKD prevalence is also expected to increase. Increased awareness and understanding of the overall CKD burden by health care teams (patients, clinicians, and pharmacist’s) is warranted so that overall care and treatment management may improve. Objectives included were assessing the drug usage in ckd, management of co morbid conditions, patient education and support during ckd transition and improving quality of life.MethodologyThis is a prospective observational study conducted over a period of six months using questionnaires as a tool. The study was conducted at Nephrology ward of AWARE GLOBAL HOSPITAL LB. NAGAR. Patients who admitted to the Nephrology ward of the hospital during a six month period from October 2016 to March 2017 are enrolled.ResultsBased on inclusion and exclusion criteria, 103patients were selected from the inpatient department over a period of 6 months for the present study. Among 103 patients The gender distribution found in the following study was males ( 65%) and females (35%),the age distribution was found to be 20-30 yrs (3.80%), 30-40yrs (9.70%), 40-50 yrs (20.38%), 50-60yrs (26.20%), 60-70yrs (27.18%), 70-80yrs (10.67%), 80-90 (1.94). Of the total 103 cases enrolled the co morbid conditions found were Hypertension (66%), diabetes mellitus (21.35%), hypothyroidism (10.60%) and urinary tract infections (1.94%). A total of 594 drugs were prescribed during the study period, out of which NSAIDS (27.03%), PPI’s (23.13%), Anti-Hypertensive (27.17%), Diuretics (12.28%), ESA’s (2.86%), Anti-hyperlipidaemias (2.02%) and Anti-diabetics (11.85%).ConclusionThe only way to manage CKD is slowing the progression of kidney deterioration. Finally we concluded that with time there happened to be change in treatment strategies and quality of life by pharmacist’s interventions. Our results were showed that the choice of treatment reasonable complying with k/DOQI Guidelines in the management of CKD. This study concludes that Anti-hypertensive’s, Anti-diabetics and Diuretics were used majorly to improvecondition and counseling was given to improve adherence to therapy and quality of life. Counseling included Dietary protein, salt, caloric restriction, decreased fluid intake, Physical exercises and Social habits for improving quality of life.Chronic kidney disease (CKD) is the 12th and 17th leading cause of death and disability globally, respectively [1]. The number of deaths due to chronic disease in India was around 5.21 million in 2008 and is expected to be 7.63 million by 2020[2]. Globally, it is one of the major cause of morbidity and mortality leading to worldwide health crisis[3].. Almost 60% of the deaths worldwide are due to CKD and ~80% of deaths occur in low and middle income countries [4]. CKD is a major problem and its prevalence will continue to rise with increasing elderly population and the number of patients with diabetes and hypertension[5].